Pengaruh Asam Fosfat Terhadap Nilai Uji Kuat Tekan Bebas Pada Stabilitas Tanah Lempung - R.A. Sri Martini; Erny Agusri; M. Faris Fisabilillah; Tri Dianita (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2026)
This study was motivated by the low bearing capacity of clay soils, which often causes structural failures in road construction in Tanjung Lalang Village, Payaraman District, Ogan Ilir Regency, South Sumatra. Clay soils tend to expand and shrink easily due to changes in moisture content, resulting in unstable ground conditions. Therefore, stabilization efforts are required to improve their strength. One alternative stabilizing agent is phosphoric acid, which chemically reacts with clay minerals to form stronger bonds, enhancing soil density and stability. This research aimed to analyze the effect of various phosphoric acid contents on the unconfined compressive strength of clay soils. The study used an experimental laboratory method with phosphoric acid variations of 0%, 6%, 7%, 8%, and 9% by dry soil weight, and curing periods of 0, 6, and 9 days. The test results showed that the addition of phosphoric acid significantly increased the unconfined compressive strength, reaching its optimum value at 7% concentration with a curing time of six days. However, excessive concentrations led to decreased strength due to reaction saturation. It can be concluded that phosphoric acid is effective as a chemical stabilizing agent to improve the strength and stability of clay soils and has potential applications for subgrade improvement in road construction projects with similar soil.